Alterations in post-movement beta event related synchronization throughout the migraine cycle: A controlled, longitudinal study. (April 2018) - Mykland, Martin Syvertsen; Bjørk, Marte Helene; Stjern, Marit; Sand, Trond
Background: The migraine brain is believed to have altered cortical excitability compared to controls and between migraine cycle phases. Our aim was to evaluate post-activation excitability through post-movement beta event related synchronization (PMBS) in sensorimotor cortices with and without sensory discrimination. Subjects and methods: We recorded EEG of 41 migraine patients and 31 healthy controls on three different days with classification of days in relation to migraine phases. During each recording, subjects performed one motor and one sensorimotor task with the right wrist. Controls and migraine patients in the interictal phase were compared with repeated measures (R-) ANOVA and two sample Student's t-test. Migraine phases were compared to the interictal phase with R-ANOVA and paired Student's t-test. Results: The difference between PMBS at the contralateral and ipsilateral sensorimotor cortex was altered throughout the migraine cycle. Compared to the interictal phase, we found decreased PMBS at the ipsilateral sensorimotor cortex in the ictal phase and increased PMBS in the preictal phase. Lower ictal PMBS was found in bilateral sensorimotor cortices in patients with right side headache predominance. Conclusion: The cyclic changes of PMBS in migraine patients may indicate that a dysfunction in deactivation and interhemispheric inhibition of the sensorimotor cortex is involved in the migraine attack cascade.